Praca i innowacyjność w warunkach zarządzania algorytmicznego i dominacji technologii cyfrowych. Wybrane konteksty kulturowe, społeczne i ekonomiczne - Drozdowicz, Jarema (Studia Edukacyjne, 2020)
The issue of algorithmic management is constituted by an array of conditions, socio-cultural and economic ones seeming to be the most important today. This article explores selected aspects and phenomena related to creativity, innovation and labor in the age of digital technologies and the domination of algorithms. The key problem in this case is the digitalization of labor, a phenomenon which also affects the creative processes and innovation. The notion of creativity shifts today towards a specific model of labor, based on and conditioned by the use of digital tools and often managed by machines, i.e. algorithms. Algorithmic labor is considered here as a social and cultural problem. The text investigates selected effects of these tendencies and highlights the important emerging issues, like the culture of incompetence for example. The outcome of this research might be used not just to improve the digital solutions in that regard, but rather to recompose the significant ideas that constitute the reflection on human agency in general.